Asuhan Keperawatan Jiwa pada Ny. W dengan Diagnosa Keperawatan Ansietas - Muspratiwi, Dea; Wilujeng Astiti, Indita; Septiana Sundari, Muhrida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the factors that influence and respond to stressors from anxiety problems experienced by caregivers of ODGJ (People with Mental Disorders) in the Work Area of ​​Puskesmas X in Bandung Regency. The method used is a case study presented in narrative form that refers to the application of Psychoeducational mental health nursing therapy. The study results indicate that the factors influencing stress are health problems (DM and gout), grief, economic problems, and family problems. However, based on observations carried out 4 times, there was a development in the response to stressors experienced by respondents. The conclusion shows an increase in coping skills and emotional well-being, emphasizing caregiver support's importance in mental health recovery. This study found the need for a comprehensive support system for caregivers of ODGJ, which improves their quality of life and treatment outcomes. Keywords: Anxiety, Mental Health Nursing, ODGJ